Characteristic and Legality of Non-Litigation Regulatory Dispute Resolution Based on Constitutional Interpretation - Winata, Muhammad Reza; Aditya, Zaka Firma (Brawijaya Law Journal, 2019)
Hyper-regulation and disharmonization of regulations is a serious challenge in Indonesia. Ministry of Law and Human Right make a breakthrough stipulates regulation on Regulatory Dispute Resolution through Non-litigation. This mechanism is unique because commonly alternative dispute resolution (ADR) used in civil law however, this instrument exercised in constitutional law. There are two research questions: First, what are the typical characteristics of non-litigation regulatory dispute resolution on Indonesia norm harmonization system; Second, how is the legality of non-litigation regulatory dispute resolution, mainly based on constitutional perspective. Author use statute, conceptual, and historical approach as research methods. The research result found the typical characteristics of non-litigation regulatory dispute resolution that most distinguish from litigation resolution: the resolution institution is Ministry under the executive branch, the final results limited only give a recommendation, and the nature of recommendation not final and binding. Next, the legality of the authority found even though only regulated at the level of Ministerial of Law and Human Rights Regulation. However, in the analysis of constitutional interpretation methods shows clearly this authority is legally based (1) Textual interpretation; (2) Structural interpretation; (3) Prudential interpretation; and (4) Consensus interpretation. Although, by nature, this process limited to resolve the conflict between norms and overregulation because it is voluntary and the result only recommendation, but the important thing is it can open alternative resolution to stimulate the harmonization and streamlining of regulations.